Finite element simulation and optimization of mechanical performance of the magnesium‐alloy biliary stent. (21st March 2022) - Zhang, Yanhong; Ni, Xiaoyu; Pan, Changwang
Abstract: A biliary stent is used to expand the bile duct during interventional treatment of biliary stricture. To reduce the complications after stent implantation, it is necessary to understand and improve the comprehensive performance of magnesium alloy biliary stents. In this study, at first, the mechanical performance of magnesium alloy biliary stent in bile ducts with different ellipticitiesis studied, and the influence of the ellipticity of bile duct on the interaction of the stent‐bile duct coupling system is better understood. Proposed results show the increment of ellipticity of the bile duct will increase the difficulty of expanding the stent. Second, to improve the mechanical performance and degradation performance of the stent simultaneously, an optimal design method based on a zero‐order algorithm is used to reduce the maximum equivalent stress on the stent effectively, to make the stress distribution more uniform, and to expand the bile duct of the lesion more effectively and uniformly. The results of this analysis and optimization are useful to predict the clinical effect of stents and to design and optimize stents for both bile duct and other non‐vascular Abstract : The mechanical performance of magnesium alloy biliary stents in bile ducts with different ellipticities is studied to understand the influence of the ellipticity of the bile duct on the interaction of the stent‐bile duct coupling system. An optimal design method based on a zero‐order algorithm is used to improve the mechanical performance and degradation performance of the stent simultaneously. The results are useful to predict the clinical effect of stents and provide references for stent design and optimization.